First-principles calculations to investigate electronic, elastic, and optical properties of one dimensional electride Y5Si3 - Ju Li; Xiao Zhang; Zhenghui Fang; Xinyu Cao; Yining Li; Chang Sun; Zhengwei Chen; Feifei Yin (Results in Physics, 2021)
Y5Si3 is an air- and water- stable electride in which part of electrons are confined in one-dimensional channels composed of Y atoms. Y5Si3 has a promoting effect on ammonia synthesis at ambient pressure due to the unique properties of these electrons at interstitial cavities (anionic electrons). Here we carry out a detailed study of electronic structure, optical and elastic properties of Y5Si3. It is found that the anionic electrons form a valence band near the Fermi energy level and it is mainly contributed by the Y-4d orbital. The calculated results of optical and mechanical properties indicated that Y5Si3 is a brittle metal and exhibits weak anisotropy. Our present work provides a comprehensive understanding on physical properties of Y5Si3.